Esforço de escuta e fadiga: estudo em pilotos de radiopatrulha aérea expostos ao ruído - Gelardi, Vera Cecilia (2019)
Introduction: Fatigue is defined as a state of impairment performance after a period of physical and / or mental effort. Objective: To evaluate the fatigue in military pilots and to compare with military who perform administrative activities, before and after the accomplishment of double task (DT). Method: The sample consisted of 22 military, 12 pilots and 10 police officers. The double task (DT) consisted of a main task (MT) of speech recognition in different signal-to-noise ratio (SNR) and a secondary task (ST), a visual memory test. Fatigue was assessed through the bipolar fatigue assessment questionnaire, originally with 14 questions, however only four questions were used, as were the only related with the reality of the group studied. The questionnaire was applied before and after the accomplishment of the double task. Statistical analysis was performed using the technique of analysis of variance in both groups, before and after the accomplishment of the double task. Results: There was no group effect on the distribution of the scores (p = 0.271) and this conclusion was valid for both times, because there was no interaction effect between group and occasion (p = 0.301). The distributions of the scores were not equal on the two occasions when the questionnaire was applied (p = 0.004), and the scores after the DT tend to be higher than before the DT. This conclusion was valid for both groups. For concentration, calm and visual fatigue, the conclusion was similar: the scores lean towards be higher after DT (p = 0.036, p = 0.033 and p = 0.038, respectively). Conclusion: The Double Task increased fatigue, concentrating difficulty, tenseness and visual fatigue in helicopter pilots (G1) and administrative police (G2). The results demonstrate that a negative SNR increases fatigue and may jeopardize flight safety